KREATIFITAS GURU DALAM MENGGUNAKAN MEDIA AUDIO VISUAL PADA PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA MUHAMMADIYAH JAYAPURA - Sigit Purwaka (WANIAMBEY : Jurnal Pendidikan Dasar Islam, 2020)
Islamic Religious Education subject are often regarded as supporting subjects. Whereas thepurpose of Islamic Religious Education is so that students can practice the knowledge of religion learnedso that faith and piety grow and behave in a laudable manner in everyday life. This could be due toteachers being less creative so students are not interested in learning Islamic Religious Education. In thecurrent technological era, a teacher is required to be creative in using learning media, especially audiovisual learning media. Aside from being a tool, audio-visual media can increase students' motivation tolearn. The higher the creativity in using audio visual media, the more students will be enthusiastic inparticipating in learning. Nevertheless challenges continue to be faced because this media cannot beused in areas that still lack electricity supply.